A new C0 higher-order layerwise finite element formulation for the analysis of laminated and sandwich plates. (1st November 2015) - Pandey, Shashank; Pradyumna, S.
Abstract: In this paper, a new layerwise plate formulation based on a C 0 higher-order finite element model is presented for static and free vibration analyses of laminated composite and sandwich plates. The proposed layerwise theory which is developed for a three layered composite plates, assumes higher-order displacement field for middle layer and first-order displacement field for top and bottom layers. Compatibility conditions are imposed at the layer interface to satisfy the interlaminar displacement continuity. An eight-noded isoparametric element is used to model the plate. The accuracy of the proposed formulation is assessed for linear static and free vibration analyses by comparing the authors' results with available 3D elasticity, finite element and analytical solutions. It has been shown here that the present finite element formulation is much simpler, straightforward and accurate for static and free vibration analyses of laminated composite and sandwich plates.